Phase, mechanical and bioactivity properties of hydroxyapatite-calcium titanate composite - Suchittra Inthong (2019)
© 2018 IOP Publishing Ltd. This research synthesizes hydroxyapatite-calcium titanate composites (HA-CT) using conventional route technique. The synthesis procedure involves two steps: (i) synthesis nanoparticle of HA and the fine powder of CT and (ii) synthesis the HA-CT composites ceramic, respectively. The nanoparticle of HA was synthesized through the co-precipitation method with control pH at 8. The fine powder of CT was prepared by molten salt synthesis. The densification, phase formation, microstructure, and mechanical properties of the HA-CT composite samples were investigated. The decreasing decomposition of HA in HA-CT composites at high temperature sintering is related to the increase of CT content. The HA-CT composites showed improvement properties of densification, Vickers hardness, Knoop hardness and Young's modulus with the maximum value as 91.20 GPa for CT 0.15 mol% in HA-CT samples. The fracture toughness resulted in data shown that the fracture toughness behavior of the HA-CT composites was controlled by the CT contents as well as grain size and porosity. The information of microstructures by SEM analysis indicated that the CT content produced a notable decrease in grain size of the HA-CT composites.